Ontogenic dietary changes in South American sea lions - Drago, M. (2009)
Stable isotopes of carbon and nitrogen in the skull bones of South American sea lions Otaria flavescens from the Chubut province (Argentina) were analysed to determine whether their feeding habits change during ontogeny. The stable isotope analysis showed that δ13C steadily increased in males and females with their developmental stage (young, first adult, adult and senile), except in senile males whose δ13C decreased to a value close to that of first adults. Pairwise comparison of bone stable isotope ratio in each developmental stage revealed differences between males and females only for the δ13C values relative to first adults and adults. Overall, results indicate that the contribution of benthic prey items to the diet of both sexes increases with the developmental stage, except in senile males, and that first adult and adult males have a more benthic diet than females at the same developmental stage. No differences exist between males and females at younger and older developmental stages. With respect to δ15N, the only difference was in young female skulls, which were more enriched than those of any other group. Consequently, the trophic level of sea lions is roughly the same throughout life, independent of the developmental stage and sex, except for young females. The growth curve analysis revealed statistically significant differences in the condylobasal length of the skull between the sea lions in both sexes of the young stage and those of the other three developmental stages considered here but not among the individuals of the three later stages. This result indicates that the dietary differences between individuals in the young stage and those in the successive stages is likely due to differences in body size, whereas dietary differences among individuals of the later three stages might be due to different foraging skills that are progressively acquired during their life span.